Planning processing in ADHD with comorbid reading disabilities is worse than in ADHD: Based on Das-Naglieri Cognitive Assessment System - Zhang, Zunwei; Feng, Junyan; Xue, Yang; Jia, Feiyong; Wang, Tiantian (Frontiers in Pediatrics, 2022)
Objective: To explore and compare the cognitive processing weakness of children with Attention deficit hyperactivity disorder (ADHD) and comorbid reading disabilities (RD) (ADHD+RD) and children with ADHD only using the Das-Naglieri Cognitive Assessment System (DN:CAS). Methods: Eighty-eight children with ADHD who visited the hospital for the first time from September 2021 to November 2021 and had a Full scale intelligence quotient (IQ) of ≥85 on the Wechsler Intelligence Scale for Children revised in China (C-WISC) were selected (Age: 6–12 years; Grade: 2–6). Based on comorbidity with RD and the subtypes of ADHD (eg. Inattention dominant type, ADHD-I, Hyperactivity/Impulse dominant type, ADHD-H and Combined type, ADHD-C), these children were divided into the ADHD+RD group (n = 30) and ADHD group (n = 58) as well as the corresponding subgroups. Clinical data on gender, age, grade, IQ scores, and DN:CAS processing scores were compared between both groups/subgroups. Spearman's correlation test was used for correlation analysis of results of interest. Results: No differences in age, grade, male-to-female ratio, verbal IQ, performance IQ, and full scale IQ were observed between the ADHD+RD group and ADHD group as well as the corresponding subgroups.(P >0.05). Children in the ADHD-C+RD subgroup had lower scores in Planning processing of DN:CAS than those in the ADHD-C subgroup (P = 0.040). However, there were no significant difference between the ADHD-I+RD subgroup and ADHD-I subgroup in Planning scores of DN:CAS assessment; The grade of ADHD-C+RD and ADHD-I+RD subgroups were positively correlated with the Planning scores of DN: CAS (r = 0.599, P = 0.030 and r = 0.508, P = 0.044 respectively). The grade of ADHD-C subgroup was positively correlated with the Planning and Simultaneous processing scores of DN: CAS (r = 0.409, P = 0.042 and r = 0.406, P = 0.044 respectively). Conclusion: Our study confirmed that children of ADHD-C with comorbid RD have a more severe Planning processing weakness compared to children with ADHD-C only. Among the children of ADHD-C+RD, ADHD-I+RD and ADHD-C, such a Planning processing impairment may improve with increasing educational skills.